An antimicrobial peptide-based colorimetric bioassay for rapid and sensitive detection of E. coli O157:H7. Issue 26 (10th March 2017) - Qiao, Zhaohui; Lei, Chunyang; Fu, Yingchun; Li, Yanbin
Abstract : A colorimetric bioassay for sensitive detection of E. coli O157:H7 using horseradish peroxidase labeled antimicrobial peptide as the signal reporter. Abstract : Rapid and sensitive detection of foodborne pathogens can effectively prevent or reduce the outbreaks of foodborne diseases. In this study, an antimicrobial peptide (AMP)-based colorimetric bioassay was developed for rapid and sensitive detection of Escherichia coli O157:H7. AMP was conjugated with horseradish peroxidase (AMP–HRP) to develop a signal reporter instead of antibody-HRP with a higher sensitivity. AMP–HRP could anchor on the surface of target bacteria rapidly through electrostatic and hydrophobic interactions. After unbound probes were removed by filtration, HRP catalyzed 3, 3′, 5, 5′-tetramethylbenzidine (TMB) to colored product, which was measured using UV-vis spectroscopy to quantify E. coli O157:H7. Due to the abundant AMP-binding sites on the surface of target bacteria, the proposed bioassay could detect E. coli O157:H7 as low as 13 cfu mL −1 in a pure culture with a linear range of 10 2 –10 5 cfu mL −1 in 45 min without pre-enrichment. Combined with an immunomagnetic capture-release procedure, sensitive and selective detection of E. coli O157:H7 in food samples was achieved.